Escravidão contemporânea à luz da crise constitucional brasileira - Sousa, Iury Alves de (Universidade Federal Rural do Semi-Árido, 2020)
The objective of this research is to analyze the scenario of the brazilian constitucional crisis under the focus of its effects on the fight against contemporary slave labor. Initially, it demonstrates the historical process of transformation of the concept of slavery to support the criteria for the consideration of a definition consistent with the constitutional precepts of valuing decent work. In the sequence, this study appreciates the influence of politics in the (in)effectiveness of labor protection norms, and how the context of precarious of labor rights is inserted in the conjuncture of a deconstitutional movement. Finally, there is a survey of parliamentary discussions on Senate Bill no. 432 of 2013, which, under the justification of regulating a measure of punishment for those who subject workers to conditions analogous to slavery, ends up prioritizing the suppression of the legal concept of contemporary slavery. Methodologically, the reasoning adopted for the development of the research is dialectical, since it considers that the brazilian problem of contemporary slavery in the scenario of a constitutional crisis is inserted in the logic of political conflict. The methodological technique used is that of theoretical research in order to conduct a historical study of political discourses, documents, journalistic articles, administrative acts and legislation. The dissertation reveals the conclusion that there is a scenario of constitutional crisis in Brazil, in which the labor market is affected, especially with regard to aspects of contemporary slavery, as illustrated in the parliamentary discussions that intended to regulate Constitutional Amendment nº 81 of 2014
Keywords: Trabalho escravo contemporâneo; Crise constitucional; Precarização do trabalho; Deconstitutional crisis; Contemporary slavery; Right to decent work; Job precarization; CIENCIAS SOCIAIS APLICADAS::DIREITO